Quantifying Residential Particulate Pollution and Human Exposure in Ibadan, Nigeria, Using Low-Cost Sensors - Aishah I. Shittu; Richard J. Pope; Kirsty J. Pringle; Stephen R. Arnold; Ailish M. Graham; Huswah O. Sideeq; Godson R. E. E. Ana; James B. McQuaid (Aerosol and Air Quality Research)
Abstract Exposure to fine particulate matter (PM2.5) pollution, both outdoors and indoors poses a significant health burden in Africa, where concentrations are often high, but there are limited measurements. Two types of low-cost sensors were used during two distinct measurement phases conducted in Ibadan, Nigeria. In Phase I, indoor and outdoor PM2.5 concentrations were measured for a two-week period in twelve households using a total of twenty-four Atmotube PRO sensors. Phase II consisted of a seven-month extended monitoring study conducted in two households (each equipped with one indoor and one outdoor sensor) and a school (1 sensor only) using five PurpleAir sensors. Across the twelve households in Phase I, daily median PM₂.₅ concentrations ranged from 12.0 to 18.0 µgm−3 indoors, and from 12.2 to 20.0 µgm−3 outdoors. The overall PM2.5 indoor-outdoor (I/O) median ratio was 0.9 indicating that outdoor levels were typically slightly higher than indoors. In January (the dry harmattan season), daily median PM2.5 concentrations were 98.0 µgm−3 indoors and 109.3 µgm−3 outdoors. In contrast, lower PM2.5 concentrations of 21.4 µgm−3 indoors and 24.5 µgm−3 outdoors were recorded in May, a rainy season. In Phase II, we find that a substantial part (~ 90%) of PM2.5 concentrations can be explained by variance in the outdoor concentrations. There was exceedance of WHO interim target IT-1 of 75 µgm−3 for PM2.5 during the dry harmattan season. The findings highlight the need for continuous air quality monitoring infrastructure to track pollutant trends and offering insights for future research. Graphical Abstract